Sistem Perdagangan Tembakau Di Sumenep Madura: Mengungkap Ketidakberdayaan Petani Terhadap Pedagang Tembakau - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The objective of this research is to study the System of Tobacco trading at Sumenep-Madura: a description of the peasant empowerless peasant vis a vis tobacco traders. Research was done in three month from June to August. Research was based on crucial problems in a system of tobacco trading, above all to the condition of peasant empowerless to tobacco traders. The result showed that the condition of trading tobacco was not healthy and made disadvantage for peasant community, are caused by the rule of game in buying tobacco considered unfair, despotic, individualistic has be done by bandol, juragan, and tauke. Example: cabutan tobacco for example and cutting high weight tobacco which over. Therefore, a rule of game like that has been made peasant empowerless. The research concluded there are two factors of the peasant empowerless in the system of tobacco trading. First, external factor, the condition of peasant's empowerless has been caused by a rule of game of tobacco's trading. Second, internal factor, the condition of empowerless that more caused by bargaining position and the unity among peasant unforceable